2020
DOI: 10.21203/rs.3.rs-36732/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic relatedness of multidrug resistant Escherichia coli isolated from humans, chickens and poultry environments

Abstract: Background: Inappropriate use of antimicrobial agents in animal production has led to the development of antimicrobial resistance (AMR) in foodborne pathogens. Transmission of AMR foodborne pathogens from reservoirs, particularly chickens to the human population do occur. Recently, we reported that occupational exposure was a risk factor for multidrug-resistant (MDR) Escherichia coli (E. coli) among poultry-workers. Here we determined the prevalence and genetic relatedness among MDR E. coli isolated from poult… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
(42 reference statements)
1
1
0
Order By: Relevance
“…E. coli isolates in this study contained many molecular polymorphisms. MLST analysis revealed that the most common types were ST155, ST10, and ST48, which was consistent with a previous report (ST155: 8/110, ST48: 8/110, ST10: 6/110) (Aworh et al, 2021). In addition, Hoek et al suggested that ST155 and ST10 were most often found in broiler farms (Van Hoek et al, 2018).…”
Section: Similar Amr In Chickens and Farmssupporting
confidence: 89%
“…E. coli isolates in this study contained many molecular polymorphisms. MLST analysis revealed that the most common types were ST155, ST10, and ST48, which was consistent with a previous report (ST155: 8/110, ST48: 8/110, ST10: 6/110) (Aworh et al, 2021). In addition, Hoek et al suggested that ST155 and ST10 were most often found in broiler farms (Van Hoek et al, 2018).…”
Section: Similar Amr In Chickens and Farmssupporting
confidence: 89%
“…The high abundance of ARGs in chicken feces and resistome sharing between chickens and humans is consistent with existing literature, much of which has focused on occupational exposures in commercial settings. For example, recent work in Nigeria identified occupational exposure to chickens as a risk factor for multidrug-resistant E. coli among poultry workers and identified similar resistance patterns and identical plasmid replicons in E. coli recovered from chickens and poultry workers [70][71][72].…”
Section: Discussionmentioning
confidence: 99%